Cakes and ale - Maugham, W. Somerset (William Somerset), 1874-1965 (Vintage International, 2000)
For Alroy Kear the task is sample: write the authorized biography of the eminently respectable Victorian novelist Edward Driffield and make it a bestseller. What he doesn't reckon on is the truth.